FEATURES OF ENGLISH LEARNERS’ NARRATIVES - Katharina Rustipa (Dinamika Bahasa dan Budaya, 2011)
This article reports the results of generic analysis on English learners’ narratives. The purposes are to reveal (1) how students use language to achieve communicative purposes, (2) how students organize thoughts into stages, (3) how students realize those thoughts linguistically. The data are obtained by randomly taking ten out of fifty students’ narratives produced when the students joined genre-based writing class in the academic year 2009/2010. The data are analyzed in two integrated parts, i.e. schematic structure analysis and lexicogrammatical analysis. The results show that the linguistic features of the learners’ Narratives are similar with those of the English native speaker’s Narrative, i.e. focus on individualized participants, use of material processes, use of relational (attributive) processes, use of past tense. However, some vocabulary and tense errors are made. Key words: Narrative, schematic structure, linguistic feature, genre, abstract, orientation, complication, evaluation, resolution, coda